The Impact of FLG Mutation and TRBV Insertion/deletion Gene Polymorphism in Molluscum Contagiosum and Papillomavirus Iraqi Patients - Saba Amer Mughir Al-Ammar (Journal of Global Pharma Technology, 2016)
Objective: Filaggrin (FLG) has very important role in the skin terminal differentiation and formation, which encoded by FLG gene. TRBV4-3, TRBV3-2 are an insertion/deletion polymorphism in human T cell receptor beta locus (TRBV).The polymorphisms in these genes have been reported in several diseases. To evaluate the impact of FLG (R501X), TRBV (I/D) polymorphisms in Molluscum contagiosum(MCV) and Papillomavirus (HPV) Iraqi patients. Material and Method: thirty one blood samples from each MCV and HPV patients and healthy control group was collected, then DNA was extracted and analyzed for FLG and TRBV genotypes and Alleles frequencies with (PCR) and by Gel electrophoreses using 1.5%, 2% Agarose concentration (respectively) was examined. Results : FLG mutations have been detected in 35% of MCV patients and in 26% of HPV patients while only 10% in the control group , in addition mutant allele (T allele) has been detected in 18% in MCV patients , 13% in HPV patients and only in 5% in the control group ,when we compared with the control group, we found that the genotype and allele frequency have significant association with MCV infection group P<0.05 , and have no significant relation with HPV infection group. For TRBV (TRBV4-3, TRBV3-2) gene polymorphism has no significant association with MCV and HPV infection groups when compared with the control group P>0.05.Conclusion: FLG mutations are associated with MCV infection while there is no significant associated with the HPV. Moreover the TRBV gene polymorphisms have no significant association with the MCV and HPV infection.Keywords Molluscum contagiosum, Human Papillomavirus, FLG (R501X), TRBV Polymorphism.